Factors affecting the biology of Telenomus isis (Polaszek) (Hymenoptera : Scelionidae), an egg parasitoid of cereal stem borers in West Africa - Chabi-Olaye, A.; Schulthess, F.; Poehling, H.M.; Borgemeister, C. (Elsevier, 2001)
This study aimed at an assessment of the potential of the egg parasitoid Telenomus isis (Polaszek) as a biological control agent of cereal stem borers. Therefore, the effects of temperature, host species, host age, and time of host deprivation on the development and the reproductive potential of T. isis were studied in the laboratory. By use of linear regression and a modified Logan model and with eggs of the noctuid Sesamia calamistis Hampson as hosts, the lower and upper thresholds for development were estimated at 13.1 and 36°C, respectively, and the optimal temperature for development was 31°C. Female T. isis had no measurable preoviposition period, and the oviposition period ranged from 3 to 5 days. Approximately 66% of the total lifetime complement of eggs of T. isis were produced within 6 h after emergence. Average total lifetime fecundity was 61.1 and 82.1 eggs per female at 21 and 28°C, respectively. Longevity of adult females was 17.1 days at 21°C and 5.2 days at 30°C. Host acceptance and suitability were tested, using nine lepidopteran borer species. Only the noctuids S. calamistis, Sesamia poephaga (Tam & Bowden), Sesamia botanephaga (Tam & Bowden), and Busseola fusca (Fuller) were successfully attacked by T. isis. Parasitism and emergence did not differ among those species, but the sex ratio (expressed as proportion of female progeny) was significantly lower on S. calamistis. An increase of the host age from 1 to 4 days significantly reduced mean parasitism from 56.7 to 23.5%. Parasitoid emergence rates and sex ratio did not vary among 1-, 2-, or 3-day-old host eggs, but both parameters were significantly lower on 4-day-old eggs. With increasing duration of host deprivation from 0 to 17 days, longevity increased from 8.5 to 18.5 days, whereas average lifetime fecundity decreased from 81.2 to 40.5 eggs per female, respectively, indicating resorption of eggs. The results are discussed and compared with life table parameters of the ubiquitous egg parasitoid Telenomus busseolae (Gahan).